New fundamental resistance exercise determinants of molecular and cellular muscle adaptations - Toigo, M.; Boutellier, U. (European Journal of Applied Physiology, 2006)
Abstract Physical activity relies on muscular force. In adult skeletal muscle, force results from the contraction of postmitotic, multinucleated myofibres of different contractile and metabolic properties. Myofibres can adapt to (patho-)physiological conditions of altered functional demand by radial growth, longitudinal growth, and regulation of fibre type functional gene modules. The adaptation's specificity depends on the distinct molecular and cellular events triggered by unique combinations of conditional cues. In order to derive effective and tailored exercise prescriptions, it must be determined (1) which mechano-biological condition leads to what molecular/cellular response, and (2) how this molecular/cellular response relates to the structural, contractile, and metabolic adaptation. It follows that a thorough mechano-biological description of the loading condition is imperative. Unfortunately, the definition of (resistance) exercise conditions in the past and present literature is insufficient. It is classically limited to load magnitude, number of repetitions and sets, rest in-between sets, number of interventions/week, and training period. In this review, we show why the current description is insufficient, and identify new determinants of quantitative and/or qualitative effects on skeletal muscle with respect to resistance exercise in healthy, adult humans. These new mandatory determinants comprise the fractional and temporal distribution of the contraction modes per repetition, duration of one repetition, rest in-between repetitions, time under tension, muscular failure, range of motion, recovery time, and anatomical definition. We strongly recommend to standardise the design and description of all future resistance exercise investigations by using the herein proposed set of 13 mechano-biological determinants (classical and new ones).